2020
DOI: 10.1017/s0007114519003453
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between residential altitude and stunting: evidence from >26 000 children living in highlands and lowlands of Ethiopia

Abstract: Little information is known about the influence of altitude on child growth in Ethiopia, where most people live in highlands. We investigated the relation of residential altitude with growth faltering (stunting) of infants and young children in Ethiopia. We also examined whether the altitude–growth relationship was independent of the influence of the dietary and non-dietary determinants of growth. We used the data of 26 976 under-5-year-old children included in the Ethiopian Demographic and Health Surveys, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 27 publications
(34 reference statements)
4
10
0
Order By: Relevance
“…This finding is in line with other studies done in Bahir Dar city (42.5%), 24 Holeta town, Oromia regional state (48.2%), 25 in Bule-Hora district (47.6%), 26 Harmaya (45.8%), 27 East Badawacho district (45.6%), 28 the high land area of Ethiopia (47%), 29 and Nigeria (47.6%). 4 However, this finding is higher than mini-EDHS 2019 (37%), 10 Amhara region report (41.3%), 29 Sodo Zuria district (24.9%), 30 Hosanna town (35.4%), 7 in Shey bench district, Southwest Ethiopia (33.3%), 22 and Korahay Zone, Somalia regional state (31.9%), 22 Sudan (24.9%), 31 and Bangladesh (41%). 5 The reason for this discrepancy might be differences in altitude.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is in line with other studies done in Bahir Dar city (42.5%), 24 Holeta town, Oromia regional state (48.2%), 25 in Bule-Hora district (47.6%), 26 Harmaya (45.8%), 27 East Badawacho district (45.6%), 28 the high land area of Ethiopia (47%), 29 and Nigeria (47.6%). 4 However, this finding is higher than mini-EDHS 2019 (37%), 10 Amhara region report (41.3%), 29 Sodo Zuria district (24.9%), 30 Hosanna town (35.4%), 7 in Shey bench district, Southwest Ethiopia (33.3%), 22 and Korahay Zone, Somalia regional state (31.9%), 22 Sudan (24.9%), 31 and Bangladesh (41%). 5 The reason for this discrepancy might be differences in altitude.…”
Section: Discussionsupporting
confidence: 91%
“…We expect that researchers studying children living in similarly remote communities (as has been documented in, for example, Tibet, Peru, and Bolivia) would find similar patterns, both because economic circumstances in these similarly remote areas are sufficiently comparable, and because our socioeconomic controls reduced the extent to which socioeconomic differences between these locations could drive regression results. Our findings suggest a moderate reduction in linear growth for children at high elevations, and they are consistent with findings reported from other locations, including Tibet (Argnani et al 2008), Argentina (Roman et al 2015), and Ethiopia (Mohammed et al 2020). Future studies that combine samples would strengthen our confidence that elevation, and not unobserved country-specific factors, is driving this pattern.…”
Section: Discussionsupporting
confidence: 91%
“…Future research for Nepal and elsewhere might attempt to account for dietary factors directly. For example, in a recent study of Ethiopian children living at high elevation, Mohammed et al (2020) found a negative association between height and elevation while controlling for household dietary diversity, measured using 24 hour recall data on 7 food groups. This suggests that the elevation relationship is robust to the inclusion of dietary measures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, altitude was found to be a significant predictor of linear growth at birth, 6 months, and 1 year for Bolivian children living at 3600 m above sea level (masl) compared to their counterparts living at 400 masl, and similar findings were later reported for a different Bolivian sample, as well as for children in the US mountain west and Tibet (Argnani et al, 2008;Dang et al, 2007;Greksa et al, 1985;Haas et al, 1982;Wang et al, 2016;Zahran et al, 2014). Studies from high-altitude areas in Argentina (Roman et al, 2015), and Ethiopia (Mohammed et al, 2020) have also found negative and statistically significant associations between altitude and linear growth, with children living beyond 2000 masl facing 28 percent greater odds of stunting, and children living at higher altitudes facing even greater risks.…”
Section: Background and Motivationmentioning
confidence: 67%